Intraperitoneally Delivered Mesenchymal Stem Cells Alleviate Experimental Colitis Through THBS1-Mediated Induction of IL-10-Competent Regulatory B Cells - Liu, Jialing; Lai, Xingqiang; Bao, Yingying; Xie, Wenfeng; Li, Zhishan; Chen, Jieying; Li, Gang; Wang, Tao; Huang, Weijun; Ma, Yuanchen; Shi, Jiahao; Zhao, Erming; et al. (Frontiers in Immunology, 2022)
Mesenchymal stem cells (MSCs) show promising therapeutic potential in treating inflammatory bowel disease (IBD), and intraperitoneal delivery of MSCs have become a more effective route for IBD treatment. However, the underlying mechanisms are still poorly understood. Here, we found that intraperitoneally delivered MSCs significantly alleviated experimental colitis. Depletion of peritoneal B cells, but not macrophages, clearly impaired the therapeutic effects of MSCs. Intraperitoneally delivered MSCs improved IBD likely by boosting the IL-10-producing B cells in the peritoneal cavity, and a single intraperitoneal injection of MSCs could significantly prevent disease severity in a recurrent mouse colitis model, with lower proinflammation cytokines and high level of IL-10. The gene expression profile revealed that thrombospondin-1 (THBS1) was dramatically upregulated in MSCs after coculture with peritoneal lavage fluid from colitis mice. Knockout of THBS1 expression in MSCs abolished their therapeutic effects in colitis and the induction of IL-10-producing B cells. Mechanistically, THBS1 modulates the activation of transforming growth factor-β (TGF-β), which combines with TGF-β receptors on B cells and contributes to IL-10 production. Blocking the interaction between THBS1 and latent TGF-β or inhibiting TGF-β receptors (TGF-βR) significantly reversed the THBS1-mediated induction of IL-10-producing B cells and the therapeutic effects on colitis. Collectively, our study revealed that intraperitoneally delivered MSCs secreted THBS1 to boost IL-10+Bregs and control the progression and recurrence of colitis, providing new insight for the prevention and treatment of IBD.